2019
DOI: 10.3390/w11112390
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Drought Regimes of the Huai River Basin, China: Probabilistic Behavior, Causes and Implications

Abstract: : Hydrological droughts were characterized using the run-length theory and the AIC (Akaike information criterion) techniques were accepted to evaluate the modeling performance of nine probability functions. In addition, the copula functions were used to describe joint probability behaviors of drought duration and drought severity for the major tributaries of the Huai River Basin (HRB) which is located in the transitional zone between humid and semi-humid climates. The results indicated that: (1) the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 51 publications
0
6
0
2
Order By: Relevance
“…In recent years, HI has shown better applicability in the study of drought, extreme drought and dryness and wetness changes in China. The calculation of HI is [8,33] HI = P PET (12) where the PET is calculated based on Thornthwaite method [34,35]. The advantage of Thornthwaite method is that it only needs the temperature and only considers the impact of surface energy on PET.…”
Section: Standardized Precipitation Index (Spi) and Humidity Index (Hi)mentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, HI has shown better applicability in the study of drought, extreme drought and dryness and wetness changes in China. The calculation of HI is [8,33] HI = P PET (12) where the PET is calculated based on Thornthwaite method [34,35]. The advantage of Thornthwaite method is that it only needs the temperature and only considers the impact of surface energy on PET.…”
Section: Standardized Precipitation Index (Spi) and Humidity Index (Hi)mentioning
confidence: 99%
“…Li et al [11] pointed out that frequency, duration, severity, and intensity of drought in the HRB would rise from 2010 to 2099. Sun et al [12] analyzed the hydrological drought regimes of the HRB and found that the frequency of hydrological droughts in the upper of the HRB was more than that in the middle of HRB under the climate change. He et al [13] analyzed the annual and seasonal SPI series of the HRB and found that there has been a drying trend in spring and autumn, and a wetting trend in summer and winter.…”
Section: Introductionmentioning
confidence: 99%
“…The HRB covers a vast plain at low elevations. The HRB is an important commodity grain base (Sun et al ., 2019a) accounting for approximately 20% of the total grain production in China, which supports about 13% of the country's total population. The concurrent droughts and cold events have a vital influence on agricultural production and human health in the HRB.…”
Section: Methodsmentioning
confidence: 99%
“…The daily streamflow series from 1956 to 2016 at 7 hydrological stations were selected to calculate ecological instream flow in the HRB (Table 1). These data were obtained from the Water Resources Research Institute of Anhui Province and Hua River China [44]. The daily precipitation of 72 meteorological stations from 1960 to 2016 were provided by China Meteorological Administration.…”
Section: Study Area and Datamentioning
confidence: 99%